Rare cause of superior vena cava syndrome: a giant bulla - Batihan, Guntug (BMJ Case Rep, 2018)
Superior vena cava syndrome (SVCS) is a group of symptoms caused by obstruction of superior vena cava. External compression caused by benign or malign processes is the most common physiopathology. We aim to present a 29-year-old man with non-productive cough, facial plethora and venous distention of the neck. Right apical tense bulla which was compress superior vena cava was detected and video-assisted thoracoscopic surgery applied. Our extensive search found out that only one report of SVCS secondary to bulla is available on Medline.